Evaluation of Artificial Surface—Urban Ecosystem Relations by Using Analytical Hierarchy Process: The Urban Landscape of Istanbul - Aksu, Gul Asli; Kirca, Simay (AVES YAYINCILIK A.Ş., 2022)
Especially in urban landscapes under intense urbanization pressure, artificial surfaces affect many components of the urban ecosystem and disrupt the flow of natural cycles. Due to the decrease in the continuity of the green system, population movement is interrupted, biodiversity decreases, the precipitation water infiltration capacity of soils and the transpiration rates decline as a result of sparse and interrupted vegetation cover, and the increase of impermeable surfaces trigger runoff rates and density. The artificial topography created by artificial surfaces, wind-shadow corridors, and urban heat island formations can be counted among further main adverse effects of the unplanned increase in artificial surfaces. Considering all these negative effects, relationships between the artificial surfaces and the green system were evaluated in our research. For this purpose, the criteria of surface cover type, surface flow direction, and slope were overlapped according to the weight ratios determined with the help of the Analytical Hierarchy Process (AHP). A map of priority areas, which enabled us to interpret the disruptions caused by artificial surfaces in the urban ecosystem, was produced. This map has been evaluated with a holistic perception to guide sustainable stormwater management and landscape planning and restoration and management processes related to the urban ecosystem. Artificial surfaces, which dominate the landscape with 62% surface cover in the research area, were assessed in terms of building blocks, transportation networks, and hardscapes, while suggestions were made for sustainable urban landscape planning.
Keywords: landscape ecology; Urbanization; Water; urbanization; Forestry; Biodiversity; Conservation; SD1-669.5; Fragmentation; Tool; landscape structure; Landscape connectivity; 15. Life on land; 6. Clean water; 12. Responsible consumption; 13. Climate action; 11. Sustainability